A Review of Digital Signature Using Different Elliptic Cryptography Technique - Singh Bhadoria, Anurag; Jain, Anurag (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Authentication and verification of digital data is important phase in internet based transaction and data access. For the authentication and verification used digital signature operation. For the operation of digital signature various cryptography techniques is used. The strength of cryptography technique measures the strength of digital signature. For the strength improvement various cryptography techniques is used such as RSA, ECC and some other bit level cryptography technique. In this paper present the review of digital signature technique basically based on elliptic curve cryptography technique. The elliptic curve cryptography technique is much stronger than other cryptography technique.Â